695 A National survey of Premedication practices for Neonatal Endotracheal Intubation and LISA (NeoPRINT Survey). (17th August 2022) - Joyce, Katie; Mimoglu, Ecem; Mohamed, Basma; Sathiyamurthy, Sundar; Banerjee, Jay
Abstract : Aims: Objective: The use of premedication during endotracheal intubation is commonplace, but there is considerable debate on their use during less invasive surfactant administration (LISA). The aim of this survey was to review the standard premedication practices preceding intubation and LISA in different neonatal units (NNUs) across the UK to understand the current practice and whether there are any alterations in relation to specific situations such as prematurity or underlying cardiac conditions. Methods: The Neonatal Pre-medication for Endotracheal Intubation (NeoPRINT) electronic survey was prepared in Qualtrics (Qualtrics XM, Utah, US), sent via email to all neonatal units in the UK. This survey comprised of 45 questions covering preferences of premedication for endotracheal intubation or LISA (vagolytics, analgesics/sedatives, and/or muscle relaxants), dosages given, repetition, adverse reactions, medication preferences in special situations (prematurity and underlying cardiac conditions), and the existence of written premedication guidelines. Responses were collected over two months (67 days). Results: 81 neonatal units responded (SCBU-18%; LNU-40% and NICU-42%). Among units that did use premedication for intubation, 78% of units used 3 or more drugs, 20% used 2 drugs, and 2% used only one. For those premedicating for LISA, 48.6% of units used 2 drugs, while 51.4% used one drug. For pre-intubation sedatives, the majority of units used fentanyl (62%) and morphine (23%), while a small proportion used propofol (6%) ( figure 1 ). Others have used morphine and fentanyl (6%), remifentanil (1%), morphine and midazolam (1%), fentanyl and ketamine (1%). Amongst muscle relaxants most use suxamethonium (81%) and atracurium (14%); as a second line majority preferred rocuronium (47%). About 92% use one repeat dose when baby is felt to be active after the first dose ( figure 1 ). SCBUs were less likely to perform LISA (10%) than LNUs (6%) or NICUs (1%). Amongst those who performed LISA, 49% used premedication whilst others didn't. Majority used lower doses of fentanyl alone (36%) or combination of fentanyl and atropine (30%). 35.4% do not use premedication for LISA. In regards to adverse effects of premedication, 23% of units reported chest rigidity/stiffness associated with opioid use. Written guidelines for premedication in intubation in were available all but one hospitals and for LISA in 80%. Premedication choices for LISA were more variable than for endotracheal intubation. There was no significant variation of preferences within networks; the main source of variation arose between the levels of the NNU and personal preferences of the physician, especially for second-line premedication choices. Conclusion: This survey demonstrates wide variation in premedication practices for endotracheal intubation of neonates. Although some variation due to physician preference is expected, especially for second-line choices, the lack of national or even regional consensus on first-line premedication was clear. Use of premedication for intubation could be standardised through national guidance driven by organisations such as BAPM. Given the use of LISA is preferable to intubation in current practice, the divisive view around premedication is striking and deserves an answer through a randomised controlled trial.